The Effectiveness of Civil Servant Competency Development Policy Implementation in Balangan Regency - Febtika Resyne; Moh. Heru Budihantho; Semuel Risal; Nuril Mawaddah (Universitas Muhammadiyah Makassar, 2026)
This study aims to analyze the implementation of Balangan Regent Regulation Number 41 of 2018 concerning Civil Servant Competency Development within the Balangan Regency Government, to identify supporting and inhibiting factors, and to assess its effectiveness. The research employs a descriptive qualitative approach using Edward III’s policy implementation model, which includes four variables: communication, resources, disposition, and bureaucratic structure. Data were collected through interviews, observations, and documentation involving ten key informants. The findings indicate that, in terms of resources and bureaucratic structure, the policy has been implemented with adequate budgetary support and comprehensive Standard Operating Procedures (SOPs). Leadership disposition reflects strong commitment to competency development initiatives. However, communication remains a challenge, particularly regarding data synchronization and inter-agency coordination. The main supporting factors include leadership commitment and regulatory legitimacy, while the inhibiting factors consist of inaccurate competency data and limited compliance among several regional work units (SKPD). Based on the indicators of policy accuracy, implementation accuracy, target accuracy, and environmental suitability, the implementation is categorized as effective. This is evidenced by the significant increase in civil servant participation in competency development programs, from 12.6% in 2021 to 72.3% in 2023.